ANALISIS TAFSIR HUKUM LA SHOLATA LIJARIL MASJID ILLA FIL MASJID - Pratiwi, Munawaroh; Zamroni, Surono; Taufik, Taufik (UIN Sumatera Utara Medan, 2024)
The importance of congregational prayer in mosques has been emphasized by Islamic religious leaders through various preaching discourses. One of the arguments supporting this practice is based on a hadith concerning neighbors' prayer places, which states that prayers should be performed in the mosque rather than neighboring places. However, there is controversy surrounding the authenticity of this hadith; scholars like Abdul Aziz Bin Baaz and Muhammad Nashiruddin al-Albani consider it weak and unsuitable as a legal basis, advocating instead for other authenticated hadiths that support congregational prayer. Despite differing opinions on specific hadiths, scholars universally agree on the importance of congregational prayer. To gain a comprehensive understanding of this issue and strengthen religious values through the practice of performing the five daily prayers in congregation at the mosque, qualitative research methods are employed. These methods facilitate a thorough analysis aligned with the research problem, objectives, and benefits. The phrase